PENINGKATAN PENGETAHUAN IBU-IBU PKK DESA TATAH LAYAP TERHADAP PENGGUNAAN OBAT BATUK DAN PILEK DI MASA PANDEMI COVID-19 - Novia Ariani; Amaliyah Wahyuni (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
The prevalence of mild coughs and colds in Tatah Layap village is quite high. The villagers mostly deal with cough and cold complaints they experience independently by buying cold cough medicines that are sold freely in pharmacies and drugstores. Easy access to pharmaceutical services around the area makes it possible to do self-medication for the community. The implementation of self-medication must be supported by knowledge and awareness from the community. The target of this activity is PKK Women in Tatah Layap Village. The method used is online extension (online). The results of the activity showed that the participants who took part in the activity were very attentive to the material provided, this shows a level of public awareness of the importance of health and the use of appropriate drugs in overcoming minor coughs and colds. Based on the results of this activity, it is hoped that the community will be wiser in using medicines for coughs and colds, wisely in choosing the right medicine in order to carry out self-medication for colds and coughs.